1983
DOI: 10.1017/s0021859600037849
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between post-parturient fatty liver and blood composition in dairy cows

Abstract: The blood composition of 45 cows with more than 20 % fat in the liver (moderate fatty liver) was compared with that of 83 cows with less than 20 % fat in the liver (mild fatty liver). The cows were sampled at 1 week after calving and were from three Friesian and one Guernsey herds. Blood concentrations of non-esterified fatty acids, bilirubin and aspartate amino-transferase were significantly elevated in cows with more than 20 % in the liver whereas concentrations of glucose, cholesterol, albumin and magnesium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
2

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 27 publications
(24 reference statements)
4
34
0
2
Order By: Relevance
“…It was found that fatty liver, ketosis, displaced abomasum, Downer and placental retention occurring around parturition were associated with a marked decrease in serum APO B-100 concentration. The major causes of the decreased serum APO B-100 level with several postparturient diseases may be associated with stresses of parturition [9,11], beginning of lactation [2-5, 14, 15, 20], and limited energy supply (hypoglycemia) [1,6,19]. Our results indicate that the level of serum APO B-100 is a useful indicator of normal or impaired lipid metabolism in the bovine liver.…”
Section: Discussionmentioning
confidence: 75%
“…It was found that fatty liver, ketosis, displaced abomasum, Downer and placental retention occurring around parturition were associated with a marked decrease in serum APO B-100 concentration. The major causes of the decreased serum APO B-100 level with several postparturient diseases may be associated with stresses of parturition [9,11], beginning of lactation [2-5, 14, 15, 20], and limited energy supply (hypoglycemia) [1,6,19]. Our results indicate that the level of serum APO B-100 is a useful indicator of normal or impaired lipid metabolism in the bovine liver.…”
Section: Discussionmentioning
confidence: 75%
“…Evidence exists that cows that develop ketosis have increased blood NEFA concentrations (51,117) and an increased TAG to glycogen ratio in the liver (22). Reid et al (87) recorded higher concentrations of 3-hydroxybutyrate in the blood of cows with moderately fatty liver (20% fat) than in cows with mildly fatty liver (less than 20% fat). Gröhn et al (39) found that severely ketotic cows had a higher percentage of fat in their livers than did healthy cows, and that the extent of fatty infiltration was positively correlated with the concentrations of ketone bodies in the blood.…”
Section: Ketosismentioning
confidence: 99%
“…Previous observations (Bogin et al, 1986;Reid et al, 1983) suggest that there is a significant negative correlation between the degree of fatty changes in the liver and the concentration of serum albumin. There is some evidence that albumin is synthesized exclusively in the rough endoplasmic reticulum of the liver, which is reduced in cows with fatty liver, (Reid and Collins, 1982;Roberts et al, 1981).…”
Section: Resultsmentioning
confidence: 91%